Evaluation Of Supplementary Feeding (Pmt) Program For Treatment Of Poor Nutrition To Children In North Aceh District - Mauludi, Mauludi; Alwi, Alwi; Alfiady, Teuku (LPPM Universitas Malikussaleh, 2021)
Malnutrition is one of the most concerning things that happened in Aceh Utara district, because it is a disgrace to the government and society. Based on data from the North Aceh Health Office, the number of sufferers of malnutrition is increasing every year. This study aims to identify and describe the evaluation of the program for handling malnutrition under five and the obstacles to evaluating the program for handling malnutrition under five by the government in North Aceh Regency. This study uses a qualitative approach with descriptive analysis research type. Data collection techniques were carried out by observation, interviews, and documentation, the data obtained were analyzed using an interactive analysis model. The results showed that government programs exist and have been implemented, namely the Supplementary Food Provision (PMT) program in the form of milk, biscuits, and multivitamins, but the number of sufferers of malnutrition is still increasing every year because the implementation is not comprehensive and uneven, which is an obstacle. In the Supplementary Feeding Program (PMT), there is an inadequate budget and a large area accompanied by a lack of supervision from the Health Office so that this program has not been carried out optimally. Research recommendations, the government can make efforts to prevent malnutrition in accordance with the rules set out in Law no. 36 of 2009 concerning health to improve the nutritional quality of individuals and communities in accordance with advances in science and technology.